Cumulative effects of manganese nanoparticle and radiofrequency radiation in male Wistar rats. (4th May 2022) - Pardhiya, Sonali; Gaharwar, Usha Singh; Gautam, Rohit; Priyadarshini, Eepsita; Nirala, Jay Prakash; Rajamani, Paulraj
Abstract: Radiofrequency radiation (RFR) is a type of non-ionizing electromagnetic radiation that includes radiowaves and microwaves with a frequency range between 3 KHz and 300 GHz. Mobile phones operate with RFR and are used tremendously resulting in increased and continuous exposure of humans to these radiations. On the other hand, nanoparticles are also being used extensively in various fields. The increasing use of radiofrequency radiations and nanoparticles has become a concern to the general public. Not many studies have reported the cumulative effect of these stressors. Hence, the present investigation was aimed to find out their cumulative effect on the mammalian system. In this study manganese nanoparticles (MNPs) were synthesized and characterized. Adult male Wistar rats were exposed to MNPs and mobile phone radiation for 45 days and their separate, as well as cumulative impact, was investigated. The effect of the MNPs and RFR on liver, kidney, and reproductive parameters were studied. Histopathology as well as liver and kidney parameters were altered when exposed to MNPs and RFR separately. However, their combined treatment did not show a synergistic toxic response in liver and kidney functions which may be due to the fact that the radiation level is low, specific absorption rate (SAR) is subthermal (0.04 W/kg) and liver and kidney are located intra abdominally, hence they would absorb comparatively lesser radiation than the testicles. MNPs and RFR both caused a highly significant decrease in sperm count, which further decreased in the combined treatment (MNPs + RFR). These results indicate that the combined treatment of these stressors can have an additive toxic response to the male reproductive system.